Toxicidade oral aguda e avaliação dos efeitos pressóricos e renais causados pela quinona oncocalixona a isolada da Auxemma oncocalyx - Costa, Laura Lícia Marcos da (2016)
Auxemma oncocalyx, of the Boraginaceae family, is a characteristic tree of the Brazilian northeast popularly known as "white pau". The chemical investigation of the hydroalcoholic extract of the stem of the plant allowed the isolation of several quinones, among them the oncocalixone A (onco-A). Pharmacological studies for this quinone indicated antitumor, antimitotic, analgesic, antiedematogenic, antiplatelet and antidiabetic activity. However, like other substances derived from the secondary metabolism of plants, quinones can cause considerable toxic reactions. The absence of toxicological data in vivo of the substance and its potential for clinical use motivated the execution of this work, which aimed to investigate the acute toxicity in vivo of the onco-A and to evaluate the pressure and renal effects of this quinone, as possible target organs of Toxicity. It was initiated with the limit dose test established in protocols 420, 423 and 425 of the OECD, oral acute toxicity, with administration of 2000 mg / kg onco-A, in female Swiss mice, for determination of LD50 and Signs of toxicity for 14 days. Plasma levels of urea, creatinine and uric acid were measured as well as histological analysis of the main organs (heart, lung and kidney) after 14 days. The effects of onco-A on mean arterial pressure were measured in anesthetized normotensive male Wistar rats submitted to cumulative concentrations of the substance (30, 100, 300 and 1000 μg / kg). The plasma levels of urea, creatinine, uric acid , TGO, TGP, alkaline phosphatase and CK-Total were evaluated in these animals, in addition to histological analysis of heart and kidneys. For evaluation of renal function, male Wistar rats were surgically excised and perfused with modified Krebs-Henseleit solution at three concentrations of onco-A (1, 3 and 10 μg / ml). The data were compared statistically considering p <0.05. Onco-A showed an LD50> 2000mg / kg, indicating that it is a low lethality substance. The substance reduced mean blood pressure significantly in the last two concentrations (300 and 1000 μg / kg). Treatment with onco-A did not alter the biochemical parameters evaluated in vivo. In the isolated kidney infusion, the onco-A increased the Perfusion Pressure (PP) in the three concentrations studied, with a proportional increase in Renal Vascular Resistance (RVR). The Glomerular Filtration Rhythm (RFG) presented transient decrease with onco-A 1 μg / mL, increase in the 3 μg / mL group, and irreversible reduction with 10 μg / mL. Urine Flow (FU) increased in all groups, while the percentages of total tubular transport of sodium (% TNa), chloride (% TCl-) and potassium (% TK +) were reduced. The histological analysis of the organs collected in the protocols showed a significant toxicity of the substance. The results showed low lethality of the substance in an acute exposure, but this induced morphological alterations indicative of tissue damage, blood pressure reduction and changes in all renal functional parameters, evidencing the toxic potential of this quinone.